Newewenhe urtnwe = Noah's ark. - Wycliffe Bible Translators ([Darwin] : Wycliffe Bible Translators, 1986)
Alyawarre reader about Noahs Ark.
Text in Alwayarre with parallel English translation.
Keywords: Noah's ark; Stories and motifs - Flood; alyawarr -- alyawarre language (C14) (NT SF53-07); Alyawarr / Alyawarre people (C14) (NT SF53-07); Alyawarr / Alyawarre language (C14) (NT SF53-07); Education - Language - Indigenous languages - Readers and primers; Northern Territory - Central NT